INVESTIGATION OF MATHEMATICS TEACHERS' OPINIONS ABOUT PROBLEM POSING - Erdik, Cengiz (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2019)
Problem posing in mathematics education is one of the most important skills. Since mathematics teachers are one of the most important parts of mathematics education and teaching, this research was conducted to evaluate their views on this important skill and the implementation process. The research was carried out by 56 mathematics teachers working at different schools with different seniority times. We evaluated the teachers’ opinions by applying content analysis. The importance of problem posing skills in mathematics education has come from knowledge and practice that teachers have.